PENINGKATAN KUALITAS KESPRO REMAJA MELALUI SOSIALISASI PUSAT INFORMASI DAN KONSELING –REMAJA (PIK-R) DI SEKOLAH MADRASAH ALIYAH MUHAMMADIYAH PEKANBARU - Trisiwi Kusuma Ningrum; Yeni Yarnita; Chairil Chairil; Isnaniar Isnaniar; Juli Widiyanto; Maswarni Maswarni; Pratiwi Gasril; Wiwik Norlita (LPPM UMRI, 2018)
The Youth Information and Counseling Center, better known as PIK-R, is one of the BKKBN programs as a forum for youth activities that is very useful for adolescents and for improving school health programs. The PIK-R socialization activity was the first step before the establishment of the PIK-R at the Muhammadiyah 1 Aliyah Madrasah in Pekanbaru. The purpose of this community service was to improve the quality of adolescent knowledge about reproductive health as an effort to plan healthy and positive adolescent lives. at Madrasah Aliyah Muhammadiyah 1 Pekanbaru with the form of information dissemination of the Youth Information & Counseling Center by providing insights on adolescent life and steps that must be taken by adolescents to become healthy and planning adolescents. The method used is lecture, discussion and question and answer. The results of dedication showed that all participants wanted the formation of PIK-R in Muhammadiyah 1 Pekanbaru Aliyah Madrasas. Thus the benefit of this service was that in addition to students getting knowledge about adolescent health which could be useful as a beginning of the formation of PIK-R at Muhammadiyah 1 Pekanbaru Islamic Senior High School.